(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Chronic endometritis is a persistent alteration of the uterine mucosa that alters receptivity and tissue regeneration; pathological abnormalities resulting in altered expression of the receptor apparatus in the uterus may be responsible for the disruption of normal endometrial function